2012
DOI: 10.1016/j.neuroimage.2012.06.075
|View full text |Cite
|
Sign up to set email alerts
|

Alpha entrainment is responsible for the attentional blink phenomenon

Abstract: The attentional blink phenomenon is the reduced ability to report a second target (T2) after identifying a first target (T1) in a rapid serial visual presentation (RSVP) of stimuli (e.g., letters), which are presented at approximately 10 items per second. Several explanations have been proposed, which focus primarily on cognitive aspects, such as attentional filter-, capacity limitation- and retrieval failure‐processes.Here, we focus on the hypothesis that an entrainment of alpha oscillations (with a frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
1
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 49 publications
(39 reference statements)
7
38
1
1
Order By: Relevance
“…Our findings are well in line with the idea that alpha plays an important role for temporal attention (Klimesch, 2012;Zauner et al, 2012). In contrast to stimulus evoked processes, attention operates already during the prestimulus period that leads to a phase alignment with the P 1 , most likely reflecting the successful temporal expectation of a stimulus.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are well in line with the idea that alpha plays an important role for temporal attention (Klimesch, 2012;Zauner et al, 2012). In contrast to stimulus evoked processes, attention operates already during the prestimulus period that leads to a phase alignment with the P 1 , most likely reflecting the successful temporal expectation of a stimulus.…”
Section: Discussionsupporting
confidence: 90%
“…The typical finding is the failure to report T2 in about 50% of the cases if the preceding T1 stimulus could be identified. In a study by Zauner et al (2012) it could be shown that the inability to report T2 is associated with a negative polarity alpha phase entrainment peristimulus to T2. This suggests that a negative polarity of alpha during stimulus presentation (of T2) may be responsible for the failure to report T2 because ongoing alpha is in counter-phase relative to the appearance of the P 1 .…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to a recent publication by Zauner et al (2012), which reported a relationship between phase entrainment and the occurrence of an AB. Specifically, Zauner and colleagues found a relationship between the occurrence of an AB and a nonuniform distribution of phase at presentation of T2.…”
Section: Coherence and The Abcontrasting
confidence: 99%
“…That is, the ssVEP response is not restricted to the stimulation frequency but may also be evident, sometimes even stronger, in the IAF (Schwab et al, 2006;Gebber, Zhong, Lewis, & Barman, 1999). Zauner et al (2012), however, take a slightly different view on this. They similarly observed that phase-locking responses in an RSVP task were not restricted to the stimulation frequency.…”
Section: Coherence During the Taskmentioning
confidence: 99%
“…Interestingly, it has been found that the phase of ongoing alpha band oscillations reflects fluctuations in visual cortical excitability, such that stimuli presented during the peak (maximum amplitude) of the alpha oscillation are better detected than stimuli that appear during the trough (minimum amplitude) (Busch et al, 2009; Mathewson et al, 2009; Zauner et al, 2012). Consistent with this, the effects of transcranial magnetic stimulation (TMS) are known to be contingent on oscillatory parameters (Rubens and Zanto, 2012), including the alpha phase when a TMS pulse is applied.…”
Section: Introductionmentioning
confidence: 99%